Investigation of smilax myosotiflora methanol extract (smme) on its safety profile, mechanism of penile erection and chemical constituents as a male rat aphrodisiac - Rosdi, Rasmaizatul Akma (2024)
Smilax myosotiflora or ‘ubi jaga’ is a popular plant in Malaysian traditional medicine as a male aphrodisiac. Scientific findings proved it possessed a peptide that increased testosterone production while the methanol extract has significantly elevated testosterone level and sexual behaviours in male rats. However, data on its toxicity effect, mechanism of action and bioactive compounds were still unknown. This study aims to investigate the S. myosotiflora methanol extract (SMME) on its safety profile, mechanism of penile erection and chemical constituents as a male rat aphrodisiac. S. myosotiflora were investigated for macronutrients, micronutrients and heavy metal ion through proximate analysis and inductively coupled plasma-mass spectrometry (ICP-MS) for the safety plant profile. Toxicity effects were evaluated through in vivo ‘Limit Test’ of acute and subacute toxicity tests using the Organization of Economic Co-Operation and Development (OECD) guidelines no. 425 and 407 accordingly. Repeated Dose 90-Day in vivo test was done on sexually experienced male (XEM) rats (Control-vehicle, SMME-800mg/kg, Viagra-5mg/kg) followed by male sexual behaviour (MSB) test and gene expression analysis to determine the mechanism of penile erection. For chemical constituents, the SMME was fractionated using liquid-liquid fractionation method prior to gas chromatography–mass spectrometry (GC-MS) and liquid chromatography–mass spectrometry/quadrupole time-of-flight (LC-MS/QTOF) analyses. Results showed that the macronutrients, macronutrients and heavy metal ion of S. myosotiflora were within safe limit. No acute/subacute toxicity effects were noted except it significantly reduced aspartate aminotransferase (AST) and increased testosterone level in SMME-treated male rats while significantly increased triglycerides in SMME-treated female rats in the subacute test. The SMME also did not cause any effect in the 90 days treatment and MSB test except significantly reduced urea in the XEM SMME versus control rats and reduced AST in the XEM SMME versus Viagra rats. Histologically, the SMME-treated XEM rats were also have higher sperm density in their cauda epididymis than the other groups. For penile erection mechanism, SMME has potential to upregulate the expression of nitric oxide synthase 3 (NOS3) and downregulate the phosphodiesterase 5 (PDE5) and 2 (PDE2) to stimulate the corpus cavernosum relaxation. Main chemical compounds in the SMME were fatty acid, flavonoid, alkaloid and terpenoid while stearamide from residual aqueous fraction (RAF) was a putative male aphrodisiac active compound. The study revealed that SMME is safe, has potential as a male aphrodisiac and could be developed as a drug of the male sexual dysfunction (MSD) provided more studies are done in the future.